2013
DOI: 10.1021/ef401118f
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Gasification of Chars Prepared from Wood and Forest Residue: A Kinetic Study

Abstract: The CO 2 gasification of chars prepared from Norway spruce and its forest residue was investigated in a thermogravimetric analyzer (TGA) at slow heating rates. The volatile content of the samples was negligible; hence the gasification reaction step could be studied alone, without the disturbance of the devolatilization reactions. Six TGA experiments were carried out for each sample with three different temperature programs in 60 and 100% CO 2 . Linear, modulated, and constant-reaction rate (CRR) temperature pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 34 publications
7
51
0
Order By: Relevance
“…Indeed, the reaction order obtained in the present study is in good agreement with the literature [47]. Kinetic studies of non-isothermal gasification was carried out by Wang et al [10,53] and the results revealed reaction orders of 0.44 and 0.58 for wood char and forest residue char, respectively, and between 0.36 and 0.42 for torrefied biomass. From another work reported by Vamvuka et al [54], which investigated the gasification of different chars from municipal solid waste, paper sludge and sewage sludge, reaction orders between 0.4 and 0.6 were also obtained.…”
Section: Kinetic Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, the reaction order obtained in the present study is in good agreement with the literature [47]. Kinetic studies of non-isothermal gasification was carried out by Wang et al [10,53] and the results revealed reaction orders of 0.44 and 0.58 for wood char and forest residue char, respectively, and between 0.36 and 0.42 for torrefied biomass. From another work reported by Vamvuka et al [54], which investigated the gasification of different chars from municipal solid waste, paper sludge and sewage sludge, reaction orders between 0.4 and 0.6 were also obtained.…”
Section: Kinetic Analysissupporting
confidence: 91%
“…This is also consistent with the fact that the amount of low reactivity secondary charcoal obtained from the condensation of tarry vapor is significantly reduced for pyrolysis of biomass under low pressure [9]. Recently, an attempt to study non-isothermal CO2 gasification kinetic of charcoals prepared at atmospheric pressure and low heating rate carbonization of Norwegian wood and forest residue was carried out by Wang et al [10]. It was found that the CO2 gasification activation energies were nearly identical for chars produced from wood and forest residues, about 221 and 218 kJ/mol, respectively.…”
Section: Introductionsupporting
confidence: 69%
“…The internal gas diffusion resistance of R 1 was not considered because the transformation of Fe 2 O 3 to Fe 3 O 4 (Equation (1)) proceeds very quickly in the initial stage of the briquette reduction. The reaction rate of the reaction given in Equation (4) is Equation (20) [36].…”
Section: Determination Of Model Parameters and Reaction Rates Of Invomentioning
confidence: 99%
“…Still this approach is not yet popular. In the field of biomass research we found the simultaneous LSQ evaluation of modulated, CRR and other type of experiments together only in works in which we participated [14][15][16][17][18][19].…”
Section: What Temperature Programs Should Be Used For a Series Of Experiments?mentioning
confidence: 99%
“…We followed the latter approach in our recent works: the cellulose component was described by Eq. (1) with the same type of f() function which was used in our combustion and gasification studies [9,[13][14][16][17][18][19].…”
Section: An Example: the Controlled Combustion Of Charcoalsmentioning
confidence: 99%